Management of Incompletely Staged Endometrial Carcinoma: A Case-Based Review - Muhammad Fakhmi; Andi Kurniadi (Indonesian Journal of Obstetrics & Gynecology Science, 2026)
Introduction: Endometrial carcinoma is the most common gynecologic malignancy in developed countries, driven by risk factors such as obesity and unopposed estrogen exposure. Early-stage detection is common due to early symptom onset. Surgical management remains the cornerstone of therapy and serves a dual role in staging the disease. This report presents the initial management of atypical endometrial hyperplasia, evaluation strategies, and treatment planning in a case of advanced-stage endometrial carcinoma with incomplete surgical staging.Case Illustration: A 50-year-old woman presented with persistent vaginal discharge one week following a supracervical hysterectomy and bilateral salpingo-oophorectomy was referred to Hasan Sadikin Hospital Bandung performed for presumed benign disease. Histopathological and immunohistochemical evaluations confirmed the diagnosis of endometrioid adenocarcinoma of endometrial origin. Although chest imaging was negative for distant metastases, further evaluation suggested local extension consistent with FIGO Stage IIIB. Given the incomplete surgical staging and advanced local disease, the patient was referred for multimodal adjuvant therapy consisting of External Beam Radiotherapy (EBRT) and vaginal brachytherapy.Conclusion: Total hysterectomy with bilateral salpingo-oophorectomy and appropriate surgical staging per FIGO guidelines represents the standard treatment for endometrial carcinoma. This case highlights that tailored adjuvant radiotherapy (EBRT and brachytherapy) is critical for effective disease management in incompletely staged high-grade or advanced-stage patients. AbstrakPendahuluan: Karsinoma endometrium merupakan kanker ginekologi yang paling sering terjadi di negara-negara maju, dengan angka kejadian yang terus meningkat secara global. Faktor risiko utama meliputi obesitas, gangguan metabolik, serta paparan estrogen tanpa antagonis progesteron. Deteksi dini sering terjadi karena gejala muncul pada tahap awal penyakit. Penanganan bedah tetap menjadi pilar utama terapi dan sekaligus berperan dalam penentuan stadium penyakit. Laporan ini memaparkan tata laksana awal hiperplasia endometrium atipikal, strategi evaluasi, serta perencanaan terapi pada kasus karsinoma endometrium stadium lanjut dengan staging bedah yang tidak lengkap.Ilustrasi Kasus: Seorang wanita berusia 50 tahun dengan diagnosis karsinoma endometrium dan riwayat histerektomi supraservikal serta salpingoovarektomi bilateral dirujuk ke Rumah Sakit Hasan Sadikin Bandung dengan keluhan keluarnya lendir berwarna kecokelatan dari vagina yang menetap satu minggu pascaoperasi. Pemeriksaan histopatologi dan imunohistokimia mengonfirmasi diagnosis adenokarsinoma endometrioid yang berasal dari endometrium. Tidak ditemukan metastasis pulmonal pada pemeriksaan radiologi. Pemeriksaan laboratorium menunjukkan anemia ringan, leukositosis, dan trombositosis. Diagnosis akhir yang ditegakkan adalah karsinoma endometrium suspek stadium IIIB menurut FIGO. Pasien kemudian dirujuk untuk menjalani radioterapi eksternal (EBRT) dan brakiterapi vagina sebagai terapi adjuvan.Kesimpulan: Histerektomi total disertai salpingoovarektomi bilateral dan staging bedah yang sesuai dengan pedoman FIGO merupakan standar penatalaksanaan karsinoma endometrium. Terapi adjuvan seperti brakiterapi vagina dan EBRT berperan penting dalam penanganan kasus dengan staging yang tidak lengkap, seperti yang dijumpai pada pasien ini.